Analisis Dampak Kebijakan Pemberlakuan Pembatasan Kegiatan Masyarakat (PPKM) Bagi Pelaku Usaha Bisnis Coffee Shop di Kabupaten Rejang Lebong - Cindy Claudia Utami; Dodi Aprianto; Mira Yanuarti (Jurnal Riset Rumpun Ilmu Tanaman, 2024)
Based on the output of "Test Statistics", it is known that Asymp. Sig (2-tailed) feasible 0.012 is smaller than <0.05, it can be said that there is an average difference between before and before the PPKM Impact, then the key H0 is rejected and H1 is accepted. In the statistical table, the calculated Z value is -2.527, while the Z table value with an alpha of 5% or 0.05 is 1.96. While the Asymp value. Sig (2 tailed) was obtained 0.012 because Z count < Z table, namely -2.527 < 1.96 or a significance value of 0.012 <0.05 according to the statistical test used, then H0 was rejected and H1 was accepted. Based on the output of "Test Statistics", it is known that Asymp. Sig (2-tailed) is feasible 0.011, smaller than <0.05, it can be said that there is an average difference that occurs at the Business Coffee Shop between before and before, it can be said that H0 is rejected and H1 is accepted. In the statistical table, the calculated Z value is -2.539, while the Z table value with an alpha of 5% or 0.05 is 1.96. While the Asymp value. Sig (2 tailed) is obtained 0.01 because Z count < Z table is -2.539 < 1.96 or